Comparison on tensile properties of hybrid and natural woven sugar palm fibre reinforced unsaturated polyester composites - Misri, Sairizal; Leman, Zulkiflle; Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan (2009)
In recent years, sugar palm fibre has been found to have great potential to be used as fibre reinforcement in polymer matrix composites. This research investigates the mechanical properties of woven glass/sugar palm fibres reinforced unsaturated polyester hybrid composite. The composite specimens made of different layer of fibres such as strand mat, natural and hand woven of sugar palm fibres. The composites were fabricated using a compression moulding technique. The tensile test was carried out in accordance to ASTM 5083 standard. The results of the experiment showed that the tensile strength, tensile modulus and elongation at break value were higher than the natural woven sugar palm fibre. As a conclusion, the usage of glass fibre had improved the tensile properties sugar palm fibre composites.